Clean language interviewing : principles and applications for researchers and practitioners - Cairns-Lee, Heather; Lawley, James; Tosey, Paul (Emerald Publishing Limited, 2022)
Clean Language Interviewing is a landmark publication that defines the field for this important practice; it is essential reading for all researchers who seek to obtain data that are faithful to the experience of the interviewee. Clean language interviewing aims to improve the ability of academic and applied researchers to minimise the introduction of the interviewer's own assumptions, to avoid 'leading' questions and instead to ask 'clean' questions. Heather Cairns-Lee, James Lawley and Paul Tosey present a state-of-the-art review of the principles and practice of clean language interviewing to make this rigorous and innovative method accessible. Using real application examples, a global group of contributors analyse the use of clean language interviewing in multiple settings including business, education, and healthcare.